The effect of recruitment and selection on employee performance - Rosita Manawari Girsang; Wico Jontarudi Tarigan; Tuahman Sipayung (Enrichment : Journal of Management, 2023)
The purpose of this research is to find out how much influence the recruitment and selection process has on the performance of employees in PD. Anugrah Simalungun. The data used in this study are primary data and secondary data. Primary data is data that is processed from the results of filling out questionnaires that have been circulated to all employees, in this case the head of the branch at PD. Anugrah Simalungun and company staff, totaling 32 people starting from administration, marketing and collectors according to what is needed in this study. The results of this study indicate that recruitment and selection in the partial hypothesis test (t test) that the recruitment variable (X1) has a significant effect on employee performance (Y), so does the selection variable (X2) which has a significant effect on employee performance (Y). Furthermore, with the joint test (F test) that the variables recruitment (X1) and selection (X2) together have a significant effect on employee performance (Y). The determination test (R2) states that recruitment and selection variables affect employee performance variables by 71.4%. The recruitment process carried out at PD. Anugrah Simalungun is good, but the recruitment process should be maintained or the recruitment method that has been applied so far should be developed to produce high employee performance. The selection process is good, but the selection process should be maintained or the selection process should be further improved in order to get prospective employees with the criteria required by PD. Anugrah Simalungun